Rancang Bangun Sistem Informasi Data Siswa Sekolah Menengah Pertama - Muhammad Irwan Syahib (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
The student data management system at SMP Negeri 4 Lambandia currently relies on conventional mechanisms through manual ledgers. The use of this manual system leads to operational hurdles, particularly regarding time efficiency in data retrieval and information management. As a solution, this research focuses on the development of a web-based information system to improve the efficiency of school data processing and distribution. By adopting the Waterfall model—which encompasses the phases of analysis, design, coding, testing, and maintenance—the resulting software has proven effective in overcoming data management challenges. The information integration offered by this system significantly facilitates faster and more accurate data search, management, and reporting processes.